Family Centered Maternity Care and Healthy Home Cadres: Review Collaborative Role in Reduce Pregnancy Risk - Marlinda, Marlinda; Septiasari, Yeti; Rahmawati, Talisa; Oktavioni, Dea (International Journal Scientific and Professional, 2025)
This review explored the collaborative roles of Family Centered Maternity Care (FCMC) and health cadres in reducing maternal risk during pregnancy. High-risk pregnancies remain a key concern contributing to maternal and infant mortality, especially in low-resource settings. FCMC has emerged as an approach that empowers families to actively participate in maternal care, while trained community health cadres facilitate early detection and health education. This paper reviewed recent studies that examined how collaboration between families, cadres, and health systems enhances antenatal care adherence, risk mitigation, and maternal well-being. Evidence shows that integrating digital tools, structured family support, and interprofessional teamwork can significantly reduce complications and improve preparedness for childbirth. It concludes that strengthening cadre-family collaboration is a critical strategy in maternal health interventions.